Intratracheal Administration of siRNA Dry Powder Targeting Vascular Endothelial Growth Factor Inhibits Lung Tumor Growth in Mice - Kei Miwata; Hirokazu Okamoto; Taku Nakashima; Daisuke Ihara; Yasushi Horimasu; Takeshi Masuda; Shintaro Miyamoto; Hiroshi Iwamoto; Kazunori Fujitaka; Hironobu Hamada; Ayumi Shibata; Takaaki Ito; et al. (Elsevier, 2018)
Inhalation therapy using small-interfering RNA (siRNA) is a potentially effective therapeutic strategy for lung cancer because of its high gene-silencing effects and sequence specificity. Previous studies reported that intratracheal administration of siRNA using pressurized metered dose inhalers or nebulizers could suppress tumor growth in murine lung metastatic models. Although dry powder inhalers are promising devices due to their low cost, good portability, and preservability, the anti-tumor effects of siRNA dry powder have not been elucidated. To evaluate the gene-silencing and anti-tumor effects of intratracheally delivered siRNA dry powder, vascular endothelial growth factor-specific siRNA (VEGF-siRNA) dry powder was administered intratracheally to mice with metastatic lung tumors consisting of B16F10 melanoma cells or Lewis lung carcinoma cells. A single intratracheal administration of VEGF-siRNA dry powder reduced VEGF levels in both bronchoalveolar lavage fluid and lung tumor tissue. Furthermore, repeated intratracheal administration of VEGF-siRNA dry powder suppressed the number of visible metastatic foci on the lung surface and tumor area in lung tissues. Taken together, intratracheal administration of siRNA dry powder could be a novel therapeutic strategy for lung cancer through the suppression of specific genes expressed in lung tumor tissue. Keywords: siRNA, dry powder, intratracheal administration, lung cancer, vascular endothelial growth factor